Evaluation of breastfeeding and infant feeding attitudes among syrian refugees in Turkey: observations of Syrian healthcare workers - Siddika Songül Yalçın; Meryem Erat Nergiz; Suzan Yalçın (BMC, 2023)
Abstract Background The influx of Syrian refugees into Turkey has highlighted the importance of supporting breastfeeding practices among this vulnerable population. We aimed to evaluate the breastfeeding and infant feeding attitudes of Syrian mothers based on the observations of Syrian healthcare workers (HCWs). Methods An online form including 31 questions was prepared in Turkish, Arabic, and English languages and distributed to HCWs, working in refugee health centers via e-mail, WhatsApp, or text message with the help of Ministry of Health in Turkey between January 2020 and March 2020. The questions were about HCWs' characteristics (occupation, region of employment, duration of employment, participation in breastfeeding counseling course) and about HCWs' observations of Syrian mothers' breastfeeding and infant feeding practices. Results A total of 876 HCWs were included in the study; about 37.3% were physicians. Only 40.0% of HCWs reported that babies were predominantly fed with breast milk in the first three days after birth, 45.2% of HCWs indicated that mothers typically used sugary water as a prelacteal food, and 30.5% believed that breastfeeding was discontinued before 12 months. The main barriers to breastfeeding identified by HCWs included the lack of education, mental and physical health issues in the mother, food insecurity, low income, inadequate housing, lack of family planning, sociocultural environment, and limited access to quality health services. For complementary feeding, 28.0% of HCWs stated early introduction and 7.4% remarked delayed. HCWs believed grains, fruits and vegetables, and dairy products as top three foods for starting complementary food (59.5%, 47.8%, and 30.3% respectively). Healthcare challenges of Syrian pregnant and lactating mothers were reported to be associated primarily with "food, finance, and housing difficulties", low maternal education, and cultural and environmental issues. HCWs recommended various solutions, such as supporting breastfeeding, offering nutrition and health support, promoting family planning, improving healthcare systems through legislation, and addressing cultural barriers. Conclusions To address breastfeeding issues among Syrian mothers, it is crucial to provide breastfeeding training to both HCWs and mothers. Expanding interventions that support breastfeeding-friendly practices, including community support and food aid for breastfeeding mothers, should also be considered to address the social determinants of breastfeeding.